The inquisition - Matharu, Taran (Matharu, Taran. Summoner, 2017)
Fletcher and Ignatius must face a trial run by the Inquisition. The trial digs up shocking information about Fletcher's past, but he's more worried about the graduating students of Vocans who are going into the orc jungles on a mission for the king. If they fail, the orcish armies will take over the Empire. Fletcher, Othello, and Sylvia risk everything to journey to the heart of Orcdom to save Hominum.